ASALIB AL-MUHASSANAT AL-LAFDHIYAH FI SUROH AL-WAQI’AH (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2024)
The miracle of the Qur'an that comes from Allah as known by linguists is seen from the aspect of language style and structure that contains meaning and suitability that can create a deep impression on the soul. So it is not surprising that some people believe that the words of the Qur'an have miracles with their eloquence that cannot be matched by anything. This study aims to find out the verses that contain saja' and jinnās and recognize the types of both in the surah al-Wāqiʽah. The method used in this study is Library research, which collects data from various references such as books, magazines, documents historic stories. The results of this study found 48 verses containing the Muhassanat of saja' style of language in Surah al-Wāqiʽah, 8 verses are included in the mutawaāzhiy course which is located in verses: 1-3, 4-5, 8-9, 28-30, 32-33, 76-77, 90-91, 93-94